A comprehensive study on the phenolic profile of widely used culinary herbs and spices: Rosemary, thyme, oregano, cinnamon, cumin and bay - Vallverdu-Queralt, Anna; Regueiro, Jorge; Martinez-Huelamo, Miriam; Rinaldi Alvarenga, Jose Fernando [UNESP]; Leal, Leone Neto; Lamuela-Raventos, Rosa M. (Elsevier B.V., 2014)
Herbs and spices have long been used to improve the flavour of food without being considered as nutritionally significant ingredients. However, the bioactive phenolic content of these plant-based products is currently attracting interest.In the present work, liquid chromatography coupled to high-resolution/accurate mass measurement LTQ-Orbitrap mass spectrometry was applied for the comprehensive identification of phenolic constituents of six of the most widely used culinary herbs (rosemary, thyme, oregano and bay) and spices (cinnamon and cumin). In this way, up to 52 compounds were identified in these culinary ingredients, some of them, as far as we know, for the first time. In order to establish the phenolic profiles of the different herbs and spices, accurate quantification of the major phenolics was performed by multiple reaction monitoring in a triple quadrupole mass spectrometer. Multivariate statistical treatment of the results allowed the assessment of distinctive features among the studied herbs and spices. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Culinary herbs; Spices; Polyphenols; Rosemary; Thyme; Oregano; Cinnamon; Bay; Cumin; LC-ESI-LTQ-Orbitrap